Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3390/w8040155
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationships between Watershed Urban Land Use and Stream Water Quality Using Linear and Generalized Additive Models

Abstract: Abstract:Although close relationships between the water quality of streams and the types of land use within their watersheds have been well-documented in previous studies, many aspects of these relationships remain unclear. We examined the relationships between urban land use and water quality using data collected from 527 sample points in five major rivers in Korea-the Han, Geum, Nakdong, Younsan, and Seomjin Rivers. Water quality data were derived from samples collected and analyzed under the guidelines of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 43 publications
(72 reference statements)
1
27
0
5
Order By: Relevance
“…An interesting feature of GAM is that it allows determination of the shape of the response curves from the data instead of fitting an a priori parametric model, making it data-driven instead of model driven [57]. GAMs have been widely applied to investigate nonlinear relationships between dependent and non-explanatory variables in various fields of study such as plant and aquatic ecology (e.g., [58]) and water quality (e.g., [59]), as well as for nonlinear relationships among biotic and bon-biotic variables in environmental settings due to complex interactions between environmental factors. Many studies have identified nonlinear relationships among components of forest ecosystems (e.g., [3,50,[60][61][62][63][64][65]).…”
Section: Linear and Nonlinear Model Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting feature of GAM is that it allows determination of the shape of the response curves from the data instead of fitting an a priori parametric model, making it data-driven instead of model driven [57]. GAMs have been widely applied to investigate nonlinear relationships between dependent and non-explanatory variables in various fields of study such as plant and aquatic ecology (e.g., [58]) and water quality (e.g., [59]), as well as for nonlinear relationships among biotic and bon-biotic variables in environmental settings due to complex interactions between environmental factors. Many studies have identified nonlinear relationships among components of forest ecosystems (e.g., [3,50,[60][61][62][63][64][65]).…”
Section: Linear and Nonlinear Model Estimationmentioning
confidence: 99%
“…In general, models with higher R 2 values explain the variance of the explanatory variables better than models with lower R 2 values. Similarly, the AIC represents the relative likelihood of delineating the true nature of the relationships among variables and smaller AIC values represent a higher likelihood of explaining the nature of the data than other models with higher AIC values; therefore, larger AIC values for models are associated with a lower probability [59]. Despite its usefulness and widespread use, AIC has been criticized for its tendency to select overly complex models [68].…”
Section: Linear and Nonlinear Model Estimationmentioning
confidence: 99%
“…Although the results are still debatable, due to limited data, the relational equation between IC and WQI for an individual pond is tested to estimate the threshold of development on the catchment area, considering the findings of Hwang et al (2016). Based on their investigation at 527 sampling sites on five major river systems in Korea, Hwang states that the linear relationships only confirmed the findings of previous studies in moderate land use conditions with 1.131.5% urban land use.…”
Section: Determining the Threshold Of Development On Catchment Areamentioning
confidence: 94%
“…Hwang et al [21] examined the relationships between urban land use and water quality in Korea. They analysed the data derived from NAEMP by using linear and generalised additive models.…”
Section: Contributionsmentioning
confidence: 99%